The Effect of Financial Distress, Audit Delay, and Audit Quality on Auditor Switching in Energy Sector Companies in Indonesia - Fatimah Az Zahra; Puspita Rama Nopiana; Asih Purwama Sari (International Journal of Economics and Management Research, 2025)
This research is motivated by the Endron scandal that has occurred, which is an energy company based in Houston, Texas, United States. The Endron scandal modified and displayed incorrect financial data which resulted in KAP having to participate in accounting for the company's financial statements. This problem has an impact on Indonesia so that there is a regulation on the replacement of auditors or KAP in auditing the company's financial statements. The purpose of this study is to determine the influence of financial distress, audit delay, and audit quality on auditor switching. This study uses a quantitative method with an associative approach and the characteristics of the problem including comparative causal research. The research population of energy sector companies listed on the IDX for the 2018-2022 period is 75 companies. The sample used was 8 companies, so that the audited financial statement data was used as many as 40 data. However, there are outliers to produce better data, so the sample is processed as many as 38 data. The results stated that financial distress had no effect on switching auditors, audit delay variables had an effect on switching auditors and audit quality had no effect on switching auditors. Meanwhile, tests conducted simultaneously showed that all variables of financial distress, audit delay, and audit quality had a significant effect on auditor switching. Finally, the author suggests that all interested parties can see information through the official website provided, so it is important to publish